DECRIMINALIZATION OF MARIJUANA POSSESSION FOR PERSONAL USE IN BRAZIL: LEGAL AND CONSTITUTIONAL ANALYSIS IN LIGHT OF LAW No. 11,343/2006 AND THE JURISPRUDENCE OF THE FEDERAL SUPREME COURT (REMUNOM, 2026)
This study analyzes the decriminalization of marijuana possession for personal use in Brazil from a legal and constitutional perspective, taking Law No. 11,343/2006 and the jurisprudential evolution of the Federal Supreme Court as its normative axis, especially in the context of Extraordinary Appeal No. 635,659. The research problem consists of investigating the extent to which maintaining the criminal classification of possession for personal use is consistent with the constitutional principles of human dignity, proportionality, minimal intervention by criminal law, and protection of public health. The general objective is to examine the legal and constitutional grounds that underpin the discussion on decriminalization, as well as to assess its possible impacts on the criminal justice system, public policies, and the protection of fundamental rights. Methodologically, this is qualitative research, of a bibliographic and documentary nature, with a legal-dogmatic approach and comparative analysis, based on specialized doctrine, national and international legislation, multilateral treaties, and judicial precedents. The study also examines foreign experiences of decriminalization, especially the models adopted in Portugal, Uruguay, the United States, and European countries, with the aim of identifying convergences, divergences, and possible contributions to the Brazilian legal context. The results indicate that criminalizing possession for personal use conflicts with constitutional principles of individual freedom, private autonomy, and proportionality in criminal law, proving to be a measure of limited effectiveness in combating drug use and controlling illicit trafficking. It is observed that decriminalization models, when associated with public health and harm reduction policies, tend to produce results that are more compatible with the protection of human rights and the rationalization of the criminal justice system. On the other hand, the study shows that the adoption of this policy requires institutional planning, clear regulatory norms, and the strengthening of public health and social assistance policies. It is concluded that the decriminalization of marijuana possession for personal use represents a reconfiguration of Brazilian criminal policy, shifting the repressive focus to an approach based on public health and the protection of fundamental rights, although its implementation requires legislative and institutional adjustments capable of ensuring legal certainty and the effectiveness of public policies. One limitation is the predominantly theoretical and normative nature of the research, indicating the need for future empirical studies to assess the concrete impacts of this policy in the Brazilian context.